3D Analysis of the Hindfoot Following Total Ankle Replacement for Varus Ankle Osteoarthritis. Issue 4 (November 2022) - Kvarda, Peter; Siegler, Lena; Horn-Lang, Tamar; Susdorf, Roman; Ruiz, Roxa; Hintermann, Beat
Category: Hindfoot; Ankle; Ankle Arthritis Introduction/Purpose: In advanced stages of varus ankle osteoarthritis (OA) progressive destabilization of the peritalar structures is common. Total ankle replacement (TAR) is a viable treatment option although data, particularly on changes in the subtalar joint position following TAR, is scarce. Therefore, we evaluated the subtalar joint using semi-automated measurements based on weightbearing cone-beam CT scans (WBCT) before and after TAR. Methods: 14 patients (15 ankles) who received TAR without additional bony procedures for varus ankle OA were analyzed using semi-automated measurements of the hindfoot based on pre-and postoperative WBCT. Pain on visual analog scale (VAS) and American Orthopedic Foot and Ankle Society Hindfoot Score (AOFAS) were assessed. Results: Five of 6 measurements showed a significant improvement including sagittal and axial talocalcaneal angle, talar horizontal inclination angle, hindfoot angle, and talar tilt. Conclusion: Besides ankle joint realignment, TAR for varus ankle OA without additional bony procedures achieved significant correction of the subtalar joint based on WBCT.